Facile synthesis and visible photocatalytic activity of single-crystal TiO2/PbTiO3 heterostructured nanofiber composites. Issue 5 (5th November 2014) - Yu, Yifeng; Ren, Zhaohui; Li, Ming; Gong, Siyu; Yin, Simin; Jiang, Shan; Li, Xiang; Wei, Xiao; Xu, Gang; Shen, Ge; Han, Gaorong
Abstract : For single-crystal TiO2 /PbTiO3 nanofiber composites, anatase TiO2 nanorods grew on the surface of tetragonal perovskite (TP) PbTiO3 nanofibers to form TiO2 /PbTiO3 heterostructures. Abstract : Single-crystal TiO2 /PbTiO3 nanofiber composites were prepared by a simple hydrothermal synthesis and annealing treatment at 650 °C, where pre-perovskite (PP) PbTiO3 (PTO) and tetrabutyl titanate (TBOT) were used as precursors. In the composites, anatase TiO2 nanorods grew on the surface of tetragonal perovskite (TP) PTO nanofibers and formed sharp TiO2 /PbTiO3 interfaces, leading to single-crystal heterostructures. The as-synthesized heterostructured nanofiber composites exhibited excellent photocatalytic activity for degradation of methylene blue (MB) under visible light irradiation ( λ > 400 nm). Especially, the composites TiO2 /PbTiO3 TBOT: 0.4 mL showed the highest photocatalytic activity, and the degradation rate of MB was 0.02392 min −1 . Such photocatalytic activity of the heterostructured nanofiber composites was supposedly attributed to the large-scale formation of the sharp interfaces, which could be critical for the photogenerated charge carrier separation and its transfer from the PTO phase to TiO2 . It is suggested that the obtained heterostructured nanofiber composites TiO2 /PbTiO3 can be exploited as an alternative visible-light-driven photocatalyst.